Knowledgeability about organic food consumption and the factors behind it - Barua, Sukanya; Satyapriya,; Kumar, Rajeev; Sangeetha, V.; Muralikrishan, L.; Wason, Monika (Frontiers in Nutrition, 2023)
The research study was conducted in National Capital Region (NCR)–Delhi (India) to ascertain the level of knowledge possessed by urban respondents about organic food consumption by structured knowledge test and determines the factors influencing it. A pilot knowledge test was administered to a preliminary sample of 42 respondents for item analysis. The final questions (items) were included in the knowledge test on the basis of difficulty index (30-80), discrimination index (≥0.20) and point-biserial correlation coefficient (≥0.235). The split-half method was applied for reliability testing and the reliability coefficient was 0.82 denotes that the test items are significantly reliable. The knowledge test was finally implemented on 1050 sample size (n=1050) and found that a major portion of respondents (62.0%) possessed very low and low to moderate levels of knowledge, whereas 23.5 and 14.5% of respondents had high and very high levels of knowledge regarding organic food. Step-wise regression analysis was done, which illustrates that six independent variables, viz. education (X2), annual income (X3), gender (X6), participation in social organization (X8), health consciousness of individual (X11) and perception about organic food (X13) could explain ~62.1% of the variation. In a nutshell, most of the respondents had the knowledge and a positive attitude towards organic food, but the majority of them possessed inadequate knowledge about various specifications of organic food. So, efforts need to make people aware of what exactly organic food is and how to identify the original.